2006
DOI: 10.1248/bpb.29.1862
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Korean Red Ginseng and Its Genuine Constituents Ginsenosides Rg3, Rf, and Rh2 in Mouse Passive Cutaneous Anaphylaxis Reaction and Contact Dermatitis Models

Abstract: Korean red ginseng (KRG, the steamed root of Panax ginseng C.A. MEYER, family Araliaceae) is frequently used as a crude substance taken orally in Asian countries as a traditional medicine. The major components of raw ginseng are ginsenosides, which contain an aglycone with a dammarane skeleton.1,2) Many types of saponins, such as ginsenosides Rb1, Rb2, Rc, and Rf, have been isolated. The ginsenosides Rg3, Rf, and Rh2 are genuine saponins in KRG and heatprocessed ginseng.3,4) Ginsenosides Rg3 and Rh2 were produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
46
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 30 publications
(21 reference statements)
3
46
0
1
Order By: Relevance
“…21) In previous studies, ginsenoside Rg 3 effectively suppressed proinflammatory cytokines, including TNF-α, IL-1β, and IL-6, in LPS-stimulated BV-2 microglial cells, 13) in Aβ-treated BV-2 microglial cells, 14) and in oxazolone applied anaphylactic mice. 22) These suppressive effects against pro-inflammatory cytokines suggested that ginsenoside Rg 3 might be associated with intracellular NF-κB which is a major transcription factor that regulates genes responsible for both the innate and adaptive immune response. 23) This study shows that ginsenoside Rg 3 significantly reduced TNF-α, IL-1β, and IL-6 mRNA in the brain tissue following systemic LPS treatment.…”
Section: Effect Of Ginsenoside Rg 3 On Microglia Activation In the mentioning
confidence: 99%
“…21) In previous studies, ginsenoside Rg 3 effectively suppressed proinflammatory cytokines, including TNF-α, IL-1β, and IL-6, in LPS-stimulated BV-2 microglial cells, 13) in Aβ-treated BV-2 microglial cells, 14) and in oxazolone applied anaphylactic mice. 22) These suppressive effects against pro-inflammatory cytokines suggested that ginsenoside Rg 3 might be associated with intracellular NF-κB which is a major transcription factor that regulates genes responsible for both the innate and adaptive immune response. 23) This study shows that ginsenoside Rg 3 significantly reduced TNF-α, IL-1β, and IL-6 mRNA in the brain tissue following systemic LPS treatment.…”
Section: Effect Of Ginsenoside Rg 3 On Microglia Activation In the mentioning
confidence: 99%
“…The magnetosphere was highly compressed due to an intense injection of electrons ∼14 min earlier (Baker et al 2002), which could enhance the local magnetic field from a few mG of the background strength to tens even hundreds of mG (Alfaro et al 2004;Tjulin et al 2004;Hall et al 2009). Although the Cluster has no single probe measurements to give nonlinear wave speeds, all four panels reveal that they excellently recorded all the bursts by double probes of high resolutions Cattell et al 2003).…”
Section: A Case Studymentioning
confidence: 99%
“…[8][9][10] 20(S)-Ginsenoside Rh2 (GRh2), with a dammarane skeleton, belongs to the protopanaxadiol family and has drawn attention in chemopreventive research. [11][12][13] Recently, researchers have found that 20(S)-GRh2 exhibits anticancer effects and could inhibit growth of several cancer cell lines and induce apoptosis in mammalian tumor cells. [14][15][16] However, the details of the signal transduction cascade involved in 20(S)-GRh2-induced death in Reh cells remaine unclear.…”
mentioning
confidence: 99%